2015
DOI: 10.1007/s40009-014-0336-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Time on Growth, Flowering and Seed Yield in Dianthus barbatus L.

Abstract: The present study was carried out to elucidate the effect of different planting dates on growth, flowering and seed production of Sweet william (Dianthus barbatus L.) during 2010-2012. Six plantings were done at an interval of 15 days starting from September 17 in both years. Plantings dates were; September 17, October 2, October 17, November 1, November 16 and December 1. The results showed that different planting dates have significant influence on vegetative, flower and seed yield characters. September 17 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
1
1
0
1
Order By: Relevance
“…The length of the inflorescence, the flowering time, the number of inflorescences, and the number of florets all have a significant impact on flowering growth characteristics and are significantly influenced by the timing of transplanting (after two weeks of germination) compared to the timing of transplanting (six weeks from germination), This may be due to the best possible climatic condition during their vegetative and flowering stages which can be reached by early planting of seedlings two weeks after germination. The experiment's findings, which were specific to early cultivation of flowers, are consistent with those of experiments on the number of flowers obtained by Amaranths [18,19,20], on the flowering period of Amaranths and with the results of [21] on the flowering period of Periwinkle and the results of [22] on the flowering period of Dianthus. The results of the total number of florets can also be explained by the increase in the number of primary and secondary branches produced by the growing plants in the first date, which produced more flower buds, which finally contributed to the increase in the number of florets per plant [19] and the number of florets per plant plays an important role in determine the quality of the inflorescences, lowercase flowers will sustain longer flower stems when the basel bods open first and subsequently the apical buds, making them more compact, gorgeous, and consumer attractive, this increases the plant's coordination value [20].…”
Section: Resultssupporting
confidence: 88%
“…The length of the inflorescence, the flowering time, the number of inflorescences, and the number of florets all have a significant impact on flowering growth characteristics and are significantly influenced by the timing of transplanting (after two weeks of germination) compared to the timing of transplanting (six weeks from germination), This may be due to the best possible climatic condition during their vegetative and flowering stages which can be reached by early planting of seedlings two weeks after germination. The experiment's findings, which were specific to early cultivation of flowers, are consistent with those of experiments on the number of flowers obtained by Amaranths [18,19,20], on the flowering period of Amaranths and with the results of [21] on the flowering period of Periwinkle and the results of [22] on the flowering period of Dianthus. The results of the total number of florets can also be explained by the increase in the number of primary and secondary branches produced by the growing plants in the first date, which produced more flower buds, which finally contributed to the increase in the number of florets per plant [19] and the number of florets per plant plays an important role in determine the quality of the inflorescences, lowercase flowers will sustain longer flower stems when the basel bods open first and subsequently the apical buds, making them more compact, gorgeous, and consumer attractive, this increases the plant's coordination value [20].…”
Section: Resultssupporting
confidence: 88%
“…For a crop of fertile seeds (as a prerequisite for longterm preservation of germination), a certain relationship has been established between the time of planting of young carnation plants and the corresponding flowering time. Sharma et al (2015) found that an early planting period of Dianthus barbatus resulted in the formation of the highest number of flowers, seed pods and seeds per pod. Dyaberi et al (2015) found significant differences between seed pod setting ability and seed number and fertility among individual phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…las cuales presentan polinización cruzada y poseen una cabeza de flor con un diámetro de 7 a 8 cm. Las flores pueden presentar colores intensos de rojo, rosa, blanco, y ser bicolor; asimismo, el número de semillas varía de 50 a 1000 en las cápsulas maduras, que pueden pesar en promedio 1,8 g. El ciclo de producción varía entre 10 a 12 semanas, dependiendo de condiciones climáticas, latitud y altitud [7].…”
Section: Introductionunclassified